Mycoelectronics: Bioprinted living fungal bioelectronics for artificial sensation - Yulu Cai; Hang Yuan; Caleb Ronders; Vittorio Mottini; Kalpana Singh; Liuxi Xing; Iha Singh; Denghao Fu; Kyla Zhao; Linux Heller; Khoi Nguyen; Bryce Waller; et al. (Proceedings of the National Academy of Sciences, 2026)
The intelligence of the human biological system is enabled by the highly distributed sensing receptors on soft skin that can distinguish various stimulations or environmental cues, thus establishing the fundamental logic of sensing and physiological regulation or response. To replicate biological perception, biohybrid systems integrating living organisms with electronics have been developed to sense environmental cues. However, current eukaryote-based biohybrids face slow growth, strict culture needs, and short lifespans, limiting real-world use. Here, we introduce fungi-based printable “ Mycoelectronics ” which are created by additive bioprinting of living fungal mycelium networks onto stretchable electronics, as a practical living thermoresponsive sensory platform. This mycoelectronics approach leverages fung‘s capabilities for rapid biological responsiveness, cultivability with exponential growth, stability and self-healing in ambient conditions, bioprintability for scalable manufacturing, and mechanical flexibility for seamless integration with soft electronics. We show that the thermal responsiveness of the fungal network arises from intrinsic cellular processes—specifically, heat-induced vacuole remodeling and fusion, which modulate ionic transport and thus the electrical conductivity of the mycelial cells and networks, enabling a rapid response. By bridging the gap between cell biology and soft electronics, the mycoelectronics device, with a living mycelial network, functions as a thermal sensation system with rapid response and intrinsic self-healing properties, autonomously restoring sensing capabilities after damage and establishing sensing pathways in hard-to-reach locations. Application demonstrations in environmental and agricultural monitoring and wearable sensing systems for humans and robots highlight the versatility of this living fungal sensor platform, suggesting promising opportunities in healthcare and the environment.